2003
DOI: 10.1111/j.1875-595x.2003.tb00749.x
|View full text |Cite
|
Sign up to set email alerts
|

An advocacy project to fluoridate toothpastes in Nepal

Abstract: The health promotion activity of advocacy for the fluoridation of toothpastes in Nepal achieved measurable gains in health promotion outcomes and intermediate outcomes. Gains in health and social outcomes will take longer to evaluate but based on epidemiological evidence and the experience of other countries increased availability of affordable fluoridated toothpaste will have a significant and ongoing impact on the oral health of the people of Nepal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 18 publications
2
34
0
Order By: Relevance
“…The income in and around Kathmandu is four to five times of that in the rural areas (1, 3). The literature supports the view that poverty is a substantial barrier to health (6).…”
Section: General Health Statussupporting
confidence: 68%
See 3 more Smart Citations
“…The income in and around Kathmandu is four to five times of that in the rural areas (1, 3). The literature supports the view that poverty is a substantial barrier to health (6).…”
Section: General Health Statussupporting
confidence: 68%
“…In Nepal there is a high amount of infectious diseases, malnutrition and high maternal and child mortality (1, 6).…”
Section: General Health Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…Experience of oral pain was high with 31% of school children reporting experiencing dental pain. Another study conducted in Nepal among 9–11 years old schoolchildren had reported that 45% of children suffered from tooth pain [13]. In the same study, it was reported that 93% of children had never visited a dentist and the decayed component constituted almost entire dmft/DMFT index.…”
Section: Discussionmentioning
confidence: 99%